HARGA SAHAM PT. UNILEVER, TBK DIPENGARUHI OLEH EARNING PER SHARE MELALUI DEBT TO EQUITY RASIO - Dyah Maharani; Eddy Sanusi Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The purpose of this study is to analyze stock prices are influenced by earnings per share through debut to equity at PT. Unilever Tbk. This study is a causal associative study with a quantitative approach. The population of this study are companies engaged in the manufacturing, marketing, and distribution of household consumer goods, beverages and food from 2013-2020 listed on the IDX. This sampling used purposive sampling technique and PT. Unilever Tbk as the research sample in this study. The data collection technique was taken from the idx website. The data analysis technique used is the path analysis model test. The results of the study show that the direct effect of partially EPS on stock prices has a positive and significant effect, DER on stock prices has a negative and significant effect, while EPS on DER has a negative and significant effect while the indirect effect of EPS on stock prices through DER has a significant effect.